HUBUNGAN TINGKAT PENGETAHUAN TENTANG CARA MEMELIHARA KESEHATAN GIGI DAN MULUT DENGAN KETERSEDIAAN ALAT MENYIKAT GIGI PADA NARAPIDANA KELAS IIB RUTAN GIANYAR TAHUN 2018 - Ida Ayu Dewi Kumala Ratih; Windha Hasiva Yudita (Jurnal Kesehatan Gigi (Dental Health Journal), 2019)
Knowledge is the result of "knowing" and this happens after someone senses a certain object. Dental health efforts need to be reviewed from the aspects of environment, knowledge, education, awareness and treatment of dental health including prevention and care. Conclusions of the study Windha Hasiva Yudita, inmates in the class IIB of the Gianyar Rutan in 2018 had a sufficient level of knowledge on how to maintain healthy oral and dental criteria. The purpose of this study was to determine the relationship between knowledge of tooth brushing and the availability of tooth brushing equipment for inmates in Class IIB of the Gianyar Detention Center in 2018. This type of cross sectional study, uses secondary data from Windha Hasiva Yudita's research. The correlation test results obtained sig .: 0,000. Conclusions of the study variable Level of Knowledge about How to Maintain Dental and Oral Health related to the Availability of Tools.